RESPONSE OF TWO MUSKMELON HYBRID TO SEAWEED AND LICORICE ROOT EXTRACT FOLIAR FERTILIZERS - Ahmed, Ahmed M.T; Saeid, Abduljabbar I. (Science Journal of University of Zakho, 2024)
A field experiment was conducted at Malta Dohuk government research farm in Dohuk province to investigate the impact of licorice root extract at three concentrations (0, 8, and 16 g.L-1) and Maxi Grow at three concentrations (0, 5, and 10 ml.L-1) on two muskmelon hybrids (ES 3111 F1 and ES 335 F1). Both hybrids received foliar sprays, and their combined effects on the growth and yield of the hybrids were examined. The experiment adhered to a randomized complete block design (RCBD) with three replicates. The results demonstrated that the influence of the muskmelon hybrids on growth and yield was not significant, except for Total Soluble Solids (TSS), which was higher in the hybrid ES 3111 F1 compared to ES 335 F1. In contrast, Maxi Grow at (10) ml.L-1 exhibited significant positive effects on all studied traits compared to the control group. Similarly, foliar application of licorice root extract at 16 g.L-1 significantly enhanced vegetative growth parameters (number of leaves per plant, number of branches per plant, with no effect on chlorophyll content), as well as stem diameter and yield-related traits such as the number and weight of fruits per plant. Notably, the combined interaction of licorice root extract at 16 g.L-1 and Maxi Grow at 10 ml.L-1 had the most favorable impact on the studied characters, particularly when applied to the ES 335 F1 hybrid. The results suggest that the use of licorice root extract and Maxi Grow is recommended for the organic production of the ES 335 F1 hybrid.